PENGARUH KELANGKAAN PUPUK SUBSIDI DAN EFISIENSI DISTRIBUSI TERHADAP PENDAPATAN PETANI DENGAN PENERAPAN NILAI – NILAI SYARIAH SEBAGAI VARIABEL MEDIATOR - Arnita, Desty; Hanif, Padlim; Arisandy, Yosy; Ujang Sanusi (LPPM STAI Muhammadiyah Probolinggo, 2026)
The scarcity of subsidized fertilizer and inefficient distribution systems are challenges that can reduce farmers’ productivity and income. This study aims to analyze the effect of subsidized fertilizer scarcity and distribution efficiency on farmers’ income, with Islamic values as an intervening variable. The research used a quantitative method, with a sample of 60 farmers in Suka Makmur Village, BTS Ulu District, Musi Rawas Regency, and was analyzed using path analysis in SPSS 27. The results showed that subsidized fertilizer scarcity and distribution efficiency simultaneously affected Islamic values, but only distribution efficiency had a significant effect. In addition, Islamic values significantly influenced farmers’ income and acted as a full mediation variable. These findings indicate that implementing the principles of justice, trustworthiness, and transparency can improve farmers’ welfare. This study recommends the digitalization of fertilizer distribution and the strengthening of Islamic economic values in agricultural assistance programs.